Microsatellite analysis of the APC gene and immunoexpression of E-cadherin, catenin, and tubulin in esophageal squamous cell carcinoma. - Nair, K; Naidoo, R; Chetty, R (2006)
The histological features that accompany the development and progression of solid tumors are known to be controlled by a distinct cascade of molecular events. One such event is the inactivation of tumor suppressor genes, such as the adenomatous polyposis coli (APC) gene. Disruption of the cadherin-catenin cell adhesion complex also plays a role in the initial steps of cancer invasion and metastasis whereas alterations in cell structural molecules, such as tubulin, may contribute to the cancer phenotype. The understanding of the status of these molecules in ESSC may provide novel markers that could impact on management of the disease. The present study examined alterations in the microsatellite sequence of the APC gene via fluorescent-based polymerase chain reaction in 100 cases of primary esophageal squamous cell carcinoma. In addition, the expression of E-cadherin, alpha- and beta-catenin, and alpha- and beta-tubulin was analyzed using immunohistochemistry. These data were then statistically compared with each other as well as the relevant clinicopathologic data. Although the APC markers (D5S210, D5S346, D5S299, and D5S82) tested did show an overall high frequency of allelic imbalance/loss of heterozygosity (62.48%) and microsatellite instability (41.27%), they did not show prognostic significance in the study cohort and were not correlated with the immunohistochemical data. The tubulin proteins showed no significant change in expression in the tumor tissue The decreased immunoreactivity of E-cadherin was statistically correlated with the presence of lymph node metastases (P = .0180). Although alpha- and beta-catenin as well as E-cadherin showed no direct prognostic value, E-cadherin may warrant further investigation as an indirect prognostic indicator by allowing more accurate prediction of lymph node metastases.